Analisis AWS, Microsoft Azure, dan GCP terhadap Latency, Throughput, IAM, dan Firewall - Islam, Ichsani; Setiawan, Antonius; Jaenul, Ariep; Mulyono, Sidik; Hertin, Revita; Wibowo, Aryo; Nisa, Khoirun; Wibisono, Sony (Universitas Harapan Bangsa, 2025)
This study evaluates the performance and security of Amazon Web Services (AWS), Microsoft Azure, and Google Cloud Platform (GCP) through technical testing and user experience surveys. Testing with Apache JMeter reveals that GCP has the highest throughput (61.7 bps) and best speed, while AWS has the lowest response time (38.16 ms) and Latency (507 ms). Performance data is presented in tables and graphs. In terms of security, AWS and Azure offer comprehensive features including role-based access control and multi-factor authentication, while GCP emphasizes network protection. Reliability analysis using Cronbach’s Alpha indicates excellent internal consistency (α > 0.9), with ANOVA tests showing significant differences in Throughput, Speed, and Firewall among providers, while other parameters show no significant differences. The findings provide insights into the strengths and weaknesses of each Cloud service provider.